Analysis of the Effects of Self-Efficacy Mediation and Organizational Commitment on the Effect of Transformational Leadership Style and Organizational Culture on Employee Performance of PT Sarana Lintas Caraka - Netty Laura Simbolon; Budi Satriyo Priyonggo (Budapest International Research and Critics University, 2022)
A company cannot develop optimally if it is not fully supported by qualified and advanced human resources within the company, including PT Sarana Lintas Caraka. The purpose of this study was to examine the mediating effect of self-efficacy and commitment to the effect of transformational leadership style and organizational culture on employee performance and job satisfaction at PT Sarana Lintas Caraka. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by SmartPLS 3.0 software. The researcher chose the census technique in the sampling technique, namely all members of the population (all PT Sarana Lintas Caraka) were used as samples in this study to examine the mediating effect and the direct influence of the related variables. The results of this study indicate that there is an effect of transformational leadership style on employee performance, there is an influence of organizational culture on employee performance, there is an influence of self-efficacy on employee performance, organizational commitment has no effect on employee performance, self-efficacy is not able to mediate the effect of transformational leadership style on employee performance. Employee performance, self-efficacy is able to mediate the effect of organizational culture on employee performance, organizational commitment is not able to mediate the effect of transformational leadership style on employee performance, organizational commitment is not able to mediate the effect of organizational culture on employee performance. The method of determining the number of respondents' eligibility is using the Hair Method which states that the respondent may be 5 to 10 times the number of research variable indicators.